Changes in standing body sway of pregnant women after long-term bed rest. (18th May 2016) - Shibayama, Y; Kuwata, T.; Yamaguchi, J.; Matsumoto, M.; Watanabe, M.; Nakano, R.; Kai, K.; Watanabe, M.; Watanabe, R.; Ohkuchi, A.; Matsubara, S.
Abstract : Pregnant women tend to fall and increased body postural instability, namely body sway, may be one of the causative factors. We had a clinical impression that pregnant women after long-term bed rest tend to fall. We hypothesised that such women may show increased body sway, which we attempted to determine. Pregnant women ( n = 161) were divided into three groups: (i) women with preterm labour after 2-week bed rest, (ii) those after 4-week bed rest, and (iii) those without bed rest or preterm labour. Body sway was analysed using stabilometry, that is, computed analysis of movement of the centre of gravity. The 3 groups fundamentally showed the same stabilometric measurements. Women with oedema showed greater medial–lateral sway than those without it. Factors other than oedema yielded no differences in stabilometric parameters. Long-term bed rest fundamentally did not increase body sway to the extent that stabilometry could reveal it. It may be prudent to consider that pregnant women with oedema tend to fall.